1990
DOI: 10.1111/j.1365-2621.1990.tb01067.x
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behaviour of wheat flour dough in twin‐screw extrusion cooking

Abstract: A capillary-type viscometer was designed to measure the apparent viscosity of the cooked wheat flour dough on-line in a twin-screw extruder. The effects of mean residence time and specific energy were studied in the ranges 20-45 s and 300-800 kJ kg-', respectively. A viscosity model was developed which accounts for effects of wall shear rate, moisture content and specific energy. It was shown that the extent of the cooking reaction is largely determined by the specific energy applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 8 publications
2
11
0
Order By: Relevance
“…The power law index values for the refined flour ranged from 0.08 to 0.27 and the consistency factor K from 8.5 × 10 3 to 46.0 × 10 3 Pa s n (Table 1) depending on the extrusion conditions. These power law index values were close to those found by Wang and others (1990) ( n = 0.15) for wheat flour using a single slit rheometer. They were nevertheless lower than those reported by Singh and Smith (1999) (0.21 < n < 0.51) for wheat flour using a single slit rheometer or by Lach (2006) ( n = 0.40) using a twin‐slit rheometer.…”
Section: Resultssupporting
confidence: 88%
“…The power law index values for the refined flour ranged from 0.08 to 0.27 and the consistency factor K from 8.5 × 10 3 to 46.0 × 10 3 Pa s n (Table 1) depending on the extrusion conditions. These power law index values were close to those found by Wang and others (1990) ( n = 0.15) for wheat flour using a single slit rheometer. They were nevertheless lower than those reported by Singh and Smith (1999) (0.21 < n < 0.51) for wheat flour using a single slit rheometer or by Lach (2006) ( n = 0.40) using a twin‐slit rheometer.…”
Section: Resultssupporting
confidence: 88%
“…Results of the M w and D hz in present work are slightly lower than those reported by Tang and Ma (2009), while the M w /M n is a little higher than theirs (Table 1). The size reduction of the large aggregates, with the improvement of the mechanical shear strength in extrusion cooking, is generally in agreement with the findings of Wang et al (1990) and Choudhury and Gautam (1999). These authors suggested that the extent of shear breakdown of starch aggregates depended on the severity of extrusion processing, which increased with increasing SME input.…”
Section: Effects Of Sme On the Molecular Weight Distribution Of Spisupporting
confidence: 85%
“…Wang et al (1990) studied the rheological behavior of wheat flour dough in twin-screw extrusion cooking, and concluded that the lower the specific energy, the higher the apparent viscosity. BattermanAzcona et al (1999) reported that corn protein bodies remained intact under mild processing conditions (SME 35-40 kJ/kg), but at higher SME (>100 kJ/kg), protein bodies were disrupted and a-zein released.…”
Section: Introductionmentioning
confidence: 99%
“…In fact. though the barrel was shorter in the present study ( 5 0 m m ) than in that of Wang et al (1990) (750mm), the specific mechanical energy was the same since the shearing section of the extruder was the same in both studies (positive 15 mm pitch and 50 mm reverse pitch sections), thus giving the same cooking of the dough. Both screw configurations differ mostly by the average residence time, which has no significant effect on the apparent viscosity of dough.…”
Section: Dough Rhrologymentioning
confidence: 53%